Validity of Hysteroscopy in Detection of Uterine Cavity Abnormalities in Women with Recurrent Pregnancy Loss - Elmandooh M (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: To explore the validity of hysteroscopy in detection of uterine cavity abnormalities in women with recurrent pregnancy loss.  Patients and Methods: This was a prospective study performed at Ain Shams University Maternity Hospital, over a 3-year period, between Jan 2013 and Jan 2016, and included 200 women who were presented for evaluation of the cause of repeated early pregnancy loss and scheduled for hysteroscopy for assessment of any uterine cavity abnormality. Participant ages ranged from 18 to 35 years. A written informed consent was obtained from all women before participation.  Results: the mean age was 29.5 ± 3.5, the mean number of previous abortion 4.1 ± 1.1, the mean number of 1st trimesteric abortion was 2 with range and the mean number of 2nd trimesteric abortion was 2. In this study, 81 % of patients were nullipara. It was also found that hysteroscopic findings were found in 41.5%. Uterine anomalies was present in 14%, including septate uterus and intrauterine adhesion (IUAs) were present in 11 %. Endometrial polyps were present in 3.5%, bicornute uterus in 3.5%, unicornuate uterus in 3.5% while submucous myomas were present in 6.5%. It was found that 17% need hysterscopic intervention including 7.5% need septectomy 4.5% need adhesiolysis, 2.5% need myomectomy while 2.5% need polypectomy.  Conclusions: Structural uterine abnormalities were detected in nearly 41.1% of patients with recurrent miscarriages, hysteroscopy has much to offer in the diagnosis of uterine cavity abnormalities, for this reason it should be included in assessment of patients with a history of recurrent miscarriage.